2010
DOI: 10.1111/j.1439-0507.2009.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnostic approaches to invasive candidiasis in critical care settings

Abstract: For the specialist, the management of invasive candidiasis infections, from diagnosis to selection of the therapeutic protocol, is often a challenge. Although early diagnosis and treatment are associated with a better prognosis, apart from cases with positive blood cultures or fluid/tissue biopsy, diagnosis is neither sensitive nor specific, relying on many different factors, clinical and laboratory findings but there is certainly a need for the specific markers in this disease. Recently, new serodiagnostic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 62 publications
(108 reference statements)
2
23
0
4
Order By: Relevance
“…The molecular methods are especially useful in detection of slow growing species such as fungi [27]. Our study also indicates the high potential of SF in the diagnosis of candidemia -we observed a signifi cantly higher detection rate of SF for C. albicans.…”
Section: Discussionsupporting
confidence: 63%
“…The molecular methods are especially useful in detection of slow growing species such as fungi [27]. Our study also indicates the high potential of SF in the diagnosis of candidemia -we observed a signifi cantly higher detection rate of SF for C. albicans.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, a commercial assay, the LightCycler SeptiFast test (Roche Molecular Systems, Basel, Switzerland), was launched in Europe [10][11][12][13]. This system is designed to detect 25 important bacterial and fungal species in whole blood in less than 6 h [14], and its sensitivity was superior to that of blood cultures [8•]. Similar data were obtained by Lehmann et al [12], who evaluated the technical and diagnostic accuracy of this commercial multiplex real-time PCR.…”
Section: Introductionmentioning
confidence: 81%
“…This test has been evaluated as a useful tool in the diagnosis of IC in bone marrow transplant recipients, hematologic or ICU patients, and users of intravenous heroin, with an overall sensitivity of 77% to 89% and a specificity of 91% to 100% [40]. It was observed that patients with positive CAGTA had a better outcome than those with negative antibodies [14]. Overall, the data are still limited, and more clinical studies are needed for sensitive evaluation.…”
Section: Antibodies Against Candida Albicans Germ Tubesmentioning
confidence: 99%
See 1 more Smart Citation
“…[39,40] Conventional PCR with panfungal primers followed by species-specifi c detection of amplicons by enzyme immunoassay or uniplex/multiplex PCR with species-specifi c primers followed by gel electrophoresis is simple and cost-effective for identifying most frequently isolated Candida species. [16,27,29,[41][42][43] Panfungal real-time PCR assays, using species-specifi c probe primers, yield faster results in a single step. However, practical application of using distinct probe primers in a single reaction is limited.…”
Section: Rapid Identifi Cation Of Blood Culture Isolates Of Candida Smentioning
confidence: 99%